The Role of Personal and Job Resources in the Relationship between Psychosocial Job Demands, Mental Strain, and Health Problems - Mayerl, Hannes; Stolz, Erwin; Waxenegger, Anja; Rásky, Éva; Freidl, Wolfgang (Frontiers in Psychology, 2016)
Recent research highlights the importance of both job resources and personal resources in the job demands-resources model. However, the results of previous studies on how these resources are related to each other and how they operate in relation to the health-impairment process of the job demands-resources model are ambiguous. Thus the authors tested an alternative model, considering job and personal resources to be domains of the same underlying factor and linking this factor to the health-impairment process. Survey data of two Austrian occupational samples (N1=8,657 and N2=9,536) were analyzed using confirmatory factor analysis and structural equation modeling. The results revealed that job and personal resources can be considered as indicators of a single resources factor which was negatively related to psychosocial job demands, mental strain, and health problems. Confirming previous studies, we further found that mental strain mediated the relationship between psychosocial job demands and health problems. Our findings suggest that interventions aimed at maintaining health in the context of work may take action on three levels: (1) the prevention of extensive job demands, (2) the reduction of work-related mental strain, and (3) the strengthening of resources.